2001
DOI: 10.1152/jappl.2001.91.6.2611
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in autonomic cardiovascular regulation: spectral, hormonal, and hemodynamic indexes

Abstract: The autonomic nervous system drives variability in heart rate, vascular tone, cardiac ejection, and arterial pressure, but gender differences in autonomic regulation of the latter three parameters are not well documented. In addition to mean values, we used spectral analysis to calculate variability in arterial pressure, heart rate (R-R interval, RRI), stroke volume, and total peripheral resistance (TPR) and measured circulating levels of catecholamines and pancreatic polypeptide in two groups of 25 +/- 1.2-yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
121
6
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 29 publications
21
121
6
9
Order By: Relevance
“…Regarding the gender differences in untrained rats, our results showed reduced sympathetic tonus and improved baroreflex sensitivity in female rats compared to previous studies on male rats (7,23,32), corroborating human data that showed sympathetic predominance in men compared to women (14,15,33). In fact, Chen and DiCarlo (16) demonstrated that female rats had a higher maximum baroreflex gain (40%) than male rats, and daily spontaneous running attenuated the arterial baroreflex regulation of HR in both sexes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the gender differences in untrained rats, our results showed reduced sympathetic tonus and improved baroreflex sensitivity in female rats compared to previous studies on male rats (7,23,32), corroborating human data that showed sympathetic predominance in men compared to women (14,15,33). In fact, Chen and DiCarlo (16) demonstrated that female rats had a higher maximum baroreflex gain (40%) than male rats, and daily spontaneous running attenuated the arterial baroreflex regulation of HR in both sexes.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding HR regulation in the resting condition, men, in contrast to women of the same age, seem to have a predominant sympathetic tone (14,15). Furthermore, studies have demonstrated a lower cardiac sympathetic modulation by spectral analysis in healthy women compared to men (15).…”
Section: Introductionmentioning
confidence: 98%
“…There are several possibilities to explain these differences in fructose-induced autonomic alterations to the heart or to the vessels: the form that fructose was provided (chow or water), the autonomic function method of evaluation, the species, and gender differences. Regarding gender differences, the higher vagal component, previously reported in females compared to males (16), is one possibility that can explain why the autonomic dysfunction began through the parasympathetic system in females. Furthermore, in the present study, the sympathetic tonus was unchanged and the vagal tonus was reduced, the autonomic balance (sympathetic/parasympathetic) was changed, leading to a sympathetic predominance, as previously reported for male fructose models (5).…”
mentioning
confidence: 90%
“…Persons over age 40 were studied because older persons have a greater prevalence of salt-sensitivity (Weinberger & Fineberg, 1991). Women only were studied due to gender differences in resting autonomic activity (Evans, Ziegler, & Patwardham, 2001). In the present study, each subject was maintained on a low sodium diet for six days followed by a high sodium diet for six days with 24-hour ambulatory blood pressure monitoring after each diet period.…”
mentioning
confidence: 99%